Antidepressant Use Amongst College Students: Findings of a Phenomenological Study - Reshmi L. Singh; Jon C. Schommer; Marcia M. Worley; Cynthia Peden-McAlpine (University of Minnesota Libraries Publishing, 2012)
Background: Depression among college students is an escalating problem and could have serious consequences such as suicide. There has been an increase in use of antidepressants on college campuses in United States. However, an in depth understanding of this phenomenon from the college student's perspective is lacking in the literature. Objective: This study examined college students' experiences and treatment decision making during their depression treatment. Methods: A longitudinal, phenomenological research methodology was completed. The participants were nine students who were taking antidepressants for diagnosis of depression. Recruitment was done via brochures placed at University bulletin boards, and a mental health clinic. Three audio taped, unstructured interviews were conducted with each participant over four months. The central question asked was: What has the experience of treating depression been for you? Analysis of text was done using Van Manen's lifeworld existentials of lived body, lived time, lived relation and lived space as the organizing framework. Results: Thirteen themes were identified within the four lifeworlds. The results showed that lived relation with providers was important for college students' decision to both initiate and continue antidepressant use. Students' role was defined in conjunction with provider's role by them as wanting to be a 'player' in their treatment decisions and needing to be 'acknowledged' as such by their providers. Conclusions: Overall, the underlying essential theme of 'autonomy' was portrayed by the students' experiential accounts of their depression treatment and treatment decision making.   Type: Original Research